From Sex Objects to Human Beings: Masking Sexual Body Parts and Humanization as Moderators to Women's Objectification. (December 2015) - Bernard, Philippe; Gervais, Sarah J.; Allen, Jill; Delmée, Alice; Klein, Olivier
Recent studies have shown that sexualized female bodies are objectified at a cognitive level. Research using the body-inversion recognition task, a robust indicator of configural (vs. analytic processing) within cognitive psychology, shows that for sexualized female bodies, people recognize upright and inverted bodies similarly rather than recognizing upright bodies better than inverted bodies (i.e., an inversion effect). This finding suggests that sexualized female bodies, like objects, are recognized analytically (rather than configurally). Nonetheless, it remains unclear when and why sexualized female bodies are objectified at a basic cognitive level. Grounded in objectification theory, the present experiments examine moderating factors that may prompt more configural processing (i.e., produce an inversion effect) and less objectification of sexualized female bodies. Replicating previous research, sexualized male bodies elicited more configural processing and less objectification compared to sexualized female bodies. We then examined whether reducing the salience of sexual body parts (Experiments 2a and 2b) and adding humanizing information about the targets (Experiment 3) causes perceivers to recognize female bodies more configurally, reducing the cognitive objectification of women. Implications for sexual objectification theory and research, as well as the role of humanizing often-dehumanized sexy women, are discussed. Additional online materials for this article are available to PWQ subscribers on PWQ's website athttp://pwq.sagepub.com/supplemental .